2021
DOI: 10.1007/s00122-021-03877-0
|View full text |Cite
|
Sign up to set email alerts
|

Status and advances in mining for blackleg (Leptosphaeria maculans) quantitative resistance (QR) in oilseed rape (Brassica napus)

Abstract: Key message Quantitative resistance (QR) loci discovered through genetic and genomic analyses are abundant in the Brassica napus genome, providing an opportunity for their utilization in enhancing blackleg resistance. Abstract Quantitative resistance (QR) has long been utilized to manage blackleg in Brassica napus (canola, oilseed rape), even before major resistance genes (R-genes) were extensively explored in breeding programmes. In contrast to R-gene-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 188 publications
(403 reference statements)
0
11
0
Order By: Relevance
“…The proteomics approach has also been used in various studies to explain the interaction between plants and fungi belonging to the biotrophic (feeding on living tissue) and necrotrophic (feeding on dead tissue) groups. Various fungal pathogens have been explored for studying these interactions, like Albugo candida , Leptosphaeria maculans , Plasmodiophora brassicae , Sclerotinia sclerotiorum , and Verticillium longisporum with various species of Brassicas including B. juncea , B. napus, B. oleracea, B. carinata , and B. rapa . …”
Section: Proteomics and Biotic Stressmentioning
confidence: 99%
“…The proteomics approach has also been used in various studies to explain the interaction between plants and fungi belonging to the biotrophic (feeding on living tissue) and necrotrophic (feeding on dead tissue) groups. Various fungal pathogens have been explored for studying these interactions, like Albugo candida , Leptosphaeria maculans , Plasmodiophora brassicae , Sclerotinia sclerotiorum , and Verticillium longisporum with various species of Brassicas including B. juncea , B. napus, B. oleracea, B. carinata , and B. rapa . …”
Section: Proteomics and Biotic Stressmentioning
confidence: 99%
“…In addition to resistance against biotrophic fungi, such as rust and powdery mildew, studies have reported the involvement of APR genes in resistance against hemibiotrophic and necrotrophic diseases, such as tan spot [ 27 ], Septoria nodorum blotch [ 28 ] and Fusarium head blight/crown rot [ 29 ] of wheat. Outside the cereals, APR genes are also known globally for their involvement in resistance against important diseases of other crops, such as maize northern leaf spot [ 30 ], canola blackleg [ 31 ], Brassica downy mildew [ 32 ], chickpea Fusarium wilt and Ascochyta blight [ 33 ], and soybean powdery mildew [ 34 ]. Beside conveying resistance against multiple pathogen strains, these APR genes play a vital role in prolonging the durability of frequently used major or seedling resistance genes when deployed along with them.…”
Section: Apr: the Wheat-rust Pathosystemmentioning
confidence: 99%
“…Although the QTLs or genomic regions conferring these resistance traits have been identified through GWAS and comparative genomic analysis, many of the underlying causal genes are unknown. This hampers our ability to unravel the underlying molecular mechanisms of these high-value resistance genes [ 31 ]. Only in the case of maize, the APR gene Helminthosporium maydis (Hm)1 for northern leaf spot was identified to encode an NADPH-dependent reductase.…”
Section: Apr: the Wheat-rust Pathosystemmentioning
confidence: 99%
“…It has been shown that climate changes, such as variation in the CO 2 concentration, temperature fluctuations and water availability, play a role in influencing disease outcomes in host plants [61]. Disease severity is also impacted by the type of disease resistance of the host, whether it is qualitative or quantitative; in Brassica blackleg disease [62][63][64][65][66][67][68], or in the qualitative type, it depends on the specific pathotype that infects the host. For example, in the B. napus-Pyrenopeziza brassicae (light leaf spot) interaction, the host resistance is specific to the isolated pathotypes [69].…”
Section: Complex Host-pathogen Interactionmentioning
confidence: 99%